Surgical Management of Intrathoracic Triton Tumors: Insights into Emerging Molecular and Epigenetic Mechanisms with a Case Series of Three Patients - Alessandro Bonis; Alberto Busetto; Federica Pezzuto; Giulia Pagliarini; Vincenzo Verzeletti; Mario Pezzella; Giorgio Cannone; Eleonora Faccioli; Marco Mammana; Giovanni Maria Comacchio; Alessandro Rebusso; Marco Schiavon; et al. (Journal of Molecular Pathology)
Malignant Triton Tumors (MTTs) are rare, high-grade malignant peripheral nerve sheath tumors (MPNSTs) frequently associated with Type 1 Neurofibromatosis (NF1). NF1, an autosomal dominant disorder, predisposes approximately 10% of affected individuals to developing MPNSTs, with 50% of these tumors occurring in NF1 patients, while others arise sporadically or in association with radiation exposure. MTTs predominantly affect anatomical regions rich in large nerves, such as the limbs, spinal root, and cranial nerves. Mediastinal presentations are exceedingly rare, posing significant diagnostic and therapeutic challenges. Current treatment strategies include surgical resection, chemotherapy, radiotherapy, and lung-sparing procedures for metastatic disease. Molecular studies of MPNSTs have revealed that NF1 mutations lead to dysregulation of the RAS signalling pathway, while epigenetic alterations (e.g., SUZ12/EED mutations) further contribute to tumor progression. Dysregulated phylogenetically conserved pathways, including Wnt/beta-catenin and non-canonical SHH signalling, play a role in sarcoma progression and Schwann cell transformation. Recent advances in miRNA research highlight their involvement in tumor invasion and progression, with dysregulated miRNA expression and chromatin remodeling contributing to the pathogenesis of these neoplasms. However, the distinct molecular profiles for MTTs remain incompletely understood. Further investigation of the genetic and epigenetic landscape is essential for improving our understanding and identifying potential therapies. Herein, we present a single-center retrospective case series of three patients with an intrathoracic triton tumor treated at our University Hospital between 2000 and 2024, serving as a starting point for future insights into MPNST pathobiology.